GAMBARAN OPTIMISME MAHASISWA UNIVERSITAS BHAYANGKARA JAKARTA RAYA YANG MENJALANI PERKULIAHAN DARING DI TENGAH PANDEMI COVID-19 - Timorora Sandha Perdhana (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2022)
The covid-19 crisis has forced education sisytems to find alternative face-to-face instrunction. As a result online lectures have been used by teachers and students. There are many problems faced by students when taking online lectures that can have negative impact on the continuity of lectures. Students must be optimistic in dealing with problems that occur during lectures in the midst of Covid-19 pandemic. This study aims to determine the level of students optimism during online lectures. This study involved 100 Bhayangkara Jakarta Raya college students. The result of this study indicate that the highest score of students optimism is at a high level with a value of 76%, and 24% of students are in the moderate category of optimism. The average level of students optimism is in the high category, meaning that students have confidence in facing all obstacle while undergoing online lectures. Keyword : Optimist, Covid-19